687 How Effective Is the 'HOT Laparoscopic Cholecystectomy Pathway' in Reducing Time to Surgery?. (19th August 2022) - Sutharsan, G; Chandra, S; Said, A; Dighe, S
Abstract: Aim: To evaluate whether the introduced 'HOT laparoscopic cholecystectomy (LC) pathway' has been effective in reducing outpatient (OP) time to surgery. Method: All patients (March-October 2021) who had a LC at either Darent Valley Hospital or Queen Mary's Sidcup were identified via an extensive database search. Patient demographics, clinical diagnosis, number of presentations, in-patient (IP) vs OP LC and days to surgery were recorded. The results were descriptively analysed and compared to findings of the audit in 2020. Results: During the study, 216 LCs were recorded, of which 31% took place as an IP and 69% occurred as an OP. Amongst the CEPOD list, 80% had a LC within 8 days of admission, in accordance with NICE guidance. 139 OP LC requests were noted, 75% included "HOT LC" in the 'to come in" (TCI) request, with an average time to OP LC of 35 days, compared to 54 days for requests which did not include "HOT LC" in the request. This was significantly quicker than the wait time of 84 days in 2019, prior to the implementation of the pathway. Conclusions: Introduction of the 'HOT LC pathway' in conjunction with greater operative capacity across 2 hospitals has resulted in earlier management of gallbladder disease and subsequently reduced length of hospital admission. Furthermore, inclusion of "HOT LC" in the TCI request significantly reduces delay in OP LC. In light of these findings, the use of the pathway should be encouraged with emphasis on the inclusion of "HOT LC" in the TCI request.